The Effect of Inside or Outside Circle on Students’ Speaking Skill In Second Grade Senior High School of Modern Cottage MA. Al-Amien Prenduan - Kulsum, Ummu; Ahmadi (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2025)
This study investigates the effect of the Inside or Outside Circle strategy on students’ speaking skill at the second grade of MA Al-Amien Prenduan. Inside or Outside Circle, one of Kagan’s cooperative learning structures, provides students with opportunities to interact with various partners and practice oral communication in a relaxed, supportive atmosphere. This quantitative research employed a true experimental design involving 40 students divided into an experimental group and a control group. Both groups were given pre-test and post-test assessments, and the data were analyzed using a t-test. The results revealed that the experimental group showed a substantially higher improvement in speaking skill, with a gain score of +19.80, compared to +8.05 in the control group. The post-test mean score of the experimental group (79.95) was significantly higher than that of the control group (67.85). The t-test analysis produced a t-value of 7.214, which exceeded the t-table value of 2.024 at the 0.05 significance level, indicating a significant difference between the two groups. These findings confirm that the Inside or Outside Circle strategy effectively enhances students’ speaking fluency, vocabulary, pronunciation, and confidence.